Eco-friendly Fabrication of Silver Nanoparticles from Propolis Extract and Their Antimicrobial and Antioxidant Efficacy - Ahmad, Waqar; Iqbal, Iqbal; Azam, Sania; Sharif, Muhammad Nabeel; Iqbal, Talat; Ziad, Muhammad; Kokab, Aneeza; Rao, Ahmad Raza; Najiy Ullah; Imtiaz, Zoya (Indus Journal of Bioscience Research, 2025)
Chemical method synthesis nanoparticles have adverse environmental and health implications because they are toxic. Consequently, intensified efforts have been put into developing green synthesis methods for nanomaterials using plant extract for the synthesis of nanoparticles. This approach can be seen as a cheaper method and more environmentally friendly than traditional nanoparticle synthesis methods. Among the number of plant-derived materials available, propolis a by-product of honey, has been found to have potential for its use as a green reducing agent in the synthesis of nanoparticles. Propolis contains many bioactive compounds, especially flavonoids, which makes propolis a suitable medium for the green synthesis of AgNPs. In the present study, propolis extract is used as the reducing agent to prepare silver nanoparticles as propolis contains antioxidants and antimicrobial properties. The preparation of the propolis extract involves the use of an extraction process that is employed to get the highest yield activity. Physic chemical techniques and NIR spectroscopy are used to deduce the chemical constitution and functional group present in the extract. After that, the synthesized silver nanoparticles are characterized using FT-IR, SEM, and XRD with the purpose of structural, morphological, and compositional analysis. These analytical tools offer useful structural details about the synthesized nanoparticles such as size, morphology, and crystallinity to assess their suitability in applications including; medicine and the environment. Thus the present study presents an efficient green method for the synthesis of nanoparticles that is credible and which also employs the use of a waste product in the process.